Current status and prospects of diagnosis and treatment for esophageal cancer with supraclavicular lymph node metastasis - Cai, Qingxin; Hong, Yingji; Huang, Xuehan; Chen, Tong; Chen, Chuangzhen (Frontiers in Oncology, 2024)
Patients with supraclavicular lymph node (SLN) metastasis from esophageal cancer encounter significant variations in treatment approaches due to differences in pathological subtypes and the lack of a unified regional staging system between East Asian and Western countries. The Tiger study aims to develop an internationally recognized staging system and to delineate the extent of regional lymph node dissection. In the context of esophageal squamous cell carcinoma (SCC) with SLN metastasis, the treatment paradigms from East Asia offer valuable insights. The Japan Esophageal Society (JES) 12th edition staging system guides a tailored comprehensive treatment strategy, emphasizing either radiotherapy and chemotherapy or surgical intervention. In contrast, esophageal adenocarcinoma (AC) predominates in Western countries, where the 8th edition of the American Joint Committee on Cancer (AJCC) staging system classifies SLN metastasis as a distant metastasis, advocating for systemic therapy as the primary treatment modality. Nonetheless, compelling evidence suggests that a multidisciplinary treatment approach, incorporating either radiotherapy and chemotherapy or surgery as the initial treatment, can yield superior outcomes for these patients compared to chemotherapy alone.